Effectiveness of biomarker-based exclusion of ventilator-acquired pneumonia to reduce antibiotic use (VAPrapid-2): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Hellyer, Thomas; Anderson, Niall; Parker, Jennie; Dark, Paul; Van Den Broeck, Tina; Singh, Suveer; McMullan, Ronan; Agus, Ashley; Emerson, Lydia; Blackwood, Bronagh; Gossain, Savita; Walsh, Tim; et al.
Abstract Background Ventilator-acquired pneumonia (VAP) is a common reason for antimicrobial therapy in the intensive care unit (ICU). Biomarker-based diagnostics could improve antimicrobial stewardship through rapid exclusion of VAP. Bronchoalveloar lavage (BAL) fluid biomarkers have previously been shown to allow the exclusion of VAP with high confidence. Methods/Design This is a prospective, multi-centre, randomised, controlled trial to determine whether a rapid biomarker-based exclusion of VAP results in fewer antibiotics and improved antimicrobial management. Patients with clinically suspected VAP undergo BAL, and VAP is confirmed by growth of a potential pathogen at > 104 colony-forming units per millilitre (CFU/ml). Patients are randomised 1:1, to either a 'biomarker-guided recommendation on antibiotics' in which BAL fluid is tested for IL-1β and IL-8 in addition to routine microbiology testing, or to 'routine use of antibiotics' in which BAL undergoes routine microbiology testing only. Clinical teams are blinded to intervention until 6 hours after randomisation, when biomarker results are reported to the clinician. The primary outcome is a change in the frequency distribution of antibiotic-free days (AFD) in the 7 days following BAL. Secondary outcome measures include antibiotic use at 14 and 28 days; ventilator-free days; 28-day mortality and ICU mortality; sequential organ failure assessment (SOFA) at days 3, 7 and 14; duration of stay in critical care and the hospital; antibiotic-associated infections; and antibiotic-resistant pathogen cultures up to hospital discharge, death or 56 days. A healthcare-resource-utilisation analysis will be calculated from the duration of critical care and hospital stay. In addition, safety data will be collected with respect to performing BAL. A sample size of 210 will be required to detect a clinically significant shift in the distribution of AFD towards more patients having fewer antibiotics and therefore more AFD. Discussion This trial will test whether a rapid biomarker-based exclusion of VAP results in rapid discontinuation of antibiotics and therefore improves antibiotic management in patients with suspected VAP. Trial registration ISRCTN65937227 . Registered on 22 August 2013. ClinicalTrials.gov, NCT01972425 . Registered on 24 October 2013.